Metaphor and What is Said - WEARING, CATHERINE (Mind & language, 2006)
:  In this paper, I argue for an account of metaphorical content as what is said when a speaker utters a metaphor. First, I show that two other possibilities—the Gricean account of metaphor as implicature and the strictly semantic account developed by Josef Stern—face several serious problems. In their place, I propose an account that takes metaphorical content to cross‐cut the semantic‐pragmatic distinction. This requires re‐thinking the notion of metaphorical content, as well as the relation between the metaphorical and the literal.